(untitled) (Research, Society and Development, 2020)
Polymers of natural origin and their derivatives are currently used as biomaterials because they are easily available and their properties can be tailored to meet specific requirements. The essential oils are widely used as antimicrobials. The objective of this study was to evaluate the in-vitro antimicrobial efficiency of cellulose acetate (CA) films incorporated with the essential oils of garlic (GR) and oregano (OR) on the microorganisms Staphylococcus aureus, Escherichia coli, Listeria monocytogenes, Salmonella choleraesuis and Pseudomonas aeruginosa and characterize the films as to their mechanical, optical and structural properties. Four treatments were evaluated, Control, Film 1 (50 ml OR.100 g-1 CA) Film 2 (50 ml OR + 30 ml GR.100 g-1 CA) and Film 3 (50 ml OR + 50 ml GR.100 g-1 CA). The concentration of oils influenced the mechanical parameters of maximum load, relative deformation at maximum load and elastic modulus, resulting in weaker, less rigid and more flexible films. There was an increase in L* and b* in films incorporated with garlic and oregano essential oil. The films incorporated with a mixture of oregano and garlic essential oils exhibited inhibition against all organisms tested.